Motiejaus Kazimiero Sarbievijaus Akmens pašventinimas (Sacra Lithothesis): žanro problema - Šarkauskienė, Skirmantė (Literatūra, 2015)
The article attempts to define the genre of one of the earliest creations by Sarbievijus – Consecration of the Stone. Consecration of the Stone is a collection of poems illustrated with prints. Sarbievijus included these texts into his poetry collections, and therefore these poems are to be considered a significant part of the poet’s lyric creation. Due to formal similarity with the emblem genre (the prints correspond to icons, the inscription – to lemmas, and rhymed texts – to subscriptions), Consecration of the Stone may be analyzed as an emblematic creation.Taking into consideration the circumstances of the appearance of the creation and the peculiarities of the text itself, the author of this article tries to prove that the poems included in the collection were recited during festivities. In such case Consecration of the Stone is to be considered a dramatic creation. An important circumstance is that the creation reflects festivities that were organized by the Jesuits of Kraþiai college. Theatre and the forms common to it was the important range of the cultural programme pursueted by the Jesuits order. In addition to that, there are numerous similarities betweenConsecration of the Stone and another creation by Sarbievijus – an epithalamium Hymenodora(Wedding Gifts) – that has a number of characteristics of a dramatic creation. It includes descriptions of live pictures, and references showing that rhymed texts are speeches of characters. This is a dramatic pageant with antique mythological deities and personifications of abstract concepts expressing virtues acting as characters. Consecration of the Stone is associated with Wedding Gift through the emblematic structure (a feature typical of all theatrical activity of Jesuits), and the compositions of the reflection and the text meant for the glorification of some virtue performing the role of a character. The poems ofConsecration of the Stone feature appeals to the dedicate – the audience that sees and hears the recited texts.On the basis of the existing typology of paratheatrical works, Consecration of the Stone should be attributed to the genre of declamatory dialogue: here four personified virtues are acting, but there is no conversation between them that would serve as a means of disclosing the action.